Penerapan Amnesti Pajak (Tax Amnesty) sebagai Alternatif Pemerintah dalam Meningkatkan Pembayaran Pajak di Indonesia - Rohartati, Sri (Jurusan PIPS FKIP UMMY Solok, 2017)
National economic growth in the last few years has experienced a slowdown which led to the decline of tax revenues and reduces the availability of domestic liquidity that is needed to boost economic growth in Indonesia. While many treasures Indonesian citizens who were stationed outside the territory of Indonesia, which should be used to increase liquidity in the country and promote national economic growth. The government plans to give Tax Amnesty to Indonesian citizens (citizen) who are suspected of tax evasion abroad. Granting Tax Amnesty as the government seeks attract public funds that had been parked on the banks of other countries. Tax Amnesty Tax Amnesty program is one of the programs implemented by the government to grant amnesty to taxpayers who commit violations of tax payments in the past. The purpose of the implementation of their future taxpayers to pay taxes according to tax which is owned not manipulate taxes are delinquent and have good intentions to pay taxes.